Internal mechanical power during cycling using non-circular versus circular chainrings - Giorgi, H.; Andrews, M.; Osborne, M. (Journal of Science and Cycling, 2015)
Introduction: Non-circular Rotor Q-Rings have been shown to increase tangential force during the pedalling downstroke compared to conventional circular chainrings1, and due to this advantage, have been proposed as a potential aid in improving short-term cycling performance such as in BMX and sprint cycling races2. Some evidence exists that suggests this effect on pedal force may manifest in a change in metabolic cost over repeated revolutions during submaximal, steady-state cycling bouts using Rotor Q-Rings3. One mechanism by which a change in total metabolic cost may occur is via a change in the power required to move the limbs segments against gravitational and inertial forces through the pedal stroke (internal mechanical power, or IP) when compared to using circular chainrings (at the same external mechanical power, EP). Strutzenberger et al.1 reported an increase in joint muscle power of the hip when Q-Rings were used compared to circular chainrings at 70 and 90 rev /min, which could cause an increased IP and result in a greater total metabolic cost. The aim of this study was to further investigate the mechanical and metabolic energetics of using Q-Rings during cycling. Their effect on IP, compared to a conventional circular chainring, was assessed using a recently-proposed, multidisciplinary model for calculating IP in cycling4, which accounts for the strengths and limitations of previous biomechanical and physiological approaches. Total metabolic cost was also compared between the two chainrings for cycling over a range of workloads.